PBAT foaming material and preparation method thereof
By regulating the PBAT synthesis process and supercritical carbon dioxide foaming process, the mechanical properties control problems of PBAT foaming materials are solved, and the preparation of materials suitable for different application environments is realized, which improves its application performance in the fields of buffer packaging and shoe materials.
Patent Information
- Application Number
- CN202411530546.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
AI Technical Summary
During the foaming process, PBAT foaming materials have problems such as low crystallinity, low melt strength, narrow foam processing window and serious foam shrinkage, resulting in limited application in the fields of buffer packaging and shoe materials, and their mechanical properties are Difficult to regulate to adapt to different transportation and storage environments.
By regulating the PBAT synthesis process, changing the sequence structure and distribution of different chain segments on the molecular chain, and combining with the supercritical carbon dioxide solid foaming processing process, PBAT foaming materials with different mechanical properties are prepared to regulate their hardness and strength.
The mechanical characteristics optimization of PBAT foaming materials are achieved, and buffer packaging materials suitable for different packaging items and transportation storage environments are provided, which improves the crystallinity, melting point and cell structure of the material, and enhances its compressive strength and energy absorption efficiency.
Smart Images

Figure CN119264399A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a PBAT foam material and a preparation method thereof, belonging to the technical field of foam materials. Background Art
[0002] Foaming materials produced by physical or chemical means to produce a cellular structure inside a polymer matrix are widely used in the fields of footwear, automobiles, construction, packaging materials, etc. due to their advantages of light weight, cushioning and shock absorption, impact resistance, sound insulation and heat insulation. At present, the common foaming materials on the market are mainly polystyrene (PS) and polyurethane (PU), but PS and PU foaming materials are neither biodegradable nor require flammable and explosive alkane foaming agents that are harmful to the environment during the foaming process. Therefore, it is of great significance to prepare biodegradable foaming materials using environmentally friendly foaming technology. The preparation of foaming materials based on supercritical carbon dioxide fluid physical foaming technology is widely favored because of its advantages of being non-toxic, odorless and green and environmentally friendly.
[0003] Polybutylene terephthalate-adipate (PBAT) is a copolymer of butylene terephthalate (PBT) and butylene adipate (PBA). It is generally a polyester synthesized by a series of reactions such as esterification and polycondensation of three monomer units: 1,4-butanediol (BDO, B unit), terephthalic acid (PTA, T unit), and adipic acid (AA, A unit). It is a typical aromatic-aliphatic copolyester semi-crystalline polymer. PBAT has the characteristics of both PBT and PBA. It is a thermoplastic elastomer with a linear chain structure. It has good ductility, elongation at break, heat resistance and impact resistance, and excellent biodegradability. Therefore, PBAT is very active in the current research on biodegradable plastics and is widely used in packaging materials, sanitary products, agriculture, footwear and other fields.
[0004] Although PBAT has many excellent properties, it still has many disadvantages, such as low crystallinity, low melt strength, narrow foaming processing window, and severe foam shrinkage, which limits the application and development of PBAT in the field of foaming materials. So far, many methods such as blending, cross-linking, chain extension, grafting, and adding fillers have been widely used to improve the defects of PBAT in the foaming process. At present, there have been many research reports on supercritical foaming of biodegradable materials, but there are still some problems in using them for cushioning packaging. For example, starch-based and other polysaccharide foaming materials have low mechanical properties and high sensitivity to moisture, and lack the basic properties required for cushioning packaging materials. In addition to the characteristics of high shrinkage and low foaming ratio, the toughness and resilience, strength and hardness of pure PBAT foaming materials have an important influence on the cushioning energy absorption effect and the protection effect of the packaged objects.
[0005] When PBAT foam material is used as a packaging material, if it exhibits high toughness and high resilience, its energy absorption effect is poor, and excessive elasticity will damage the packaged object back and forth; if it exhibits low hardness and low strength, its cushioning effect is poor, and the packaged object is easily subjected to large external stress impact; if it exhibits high hardness and high strength, although its energy absorption effect is good, when subjected to external stress impact, the packaged object is more likely to be damaged by bumps or knocks of the packaging material. Therefore, by regulating the toughness and resilience, strength and hardness of PBAT foam material, it has different mechanical characteristics, which is suitable for cushioning packaging materials under different packaged items and different transportation and storage environment conditions. This is of great significance to the application of PBAT foam material in cushioning packaging, shoe materials and other fields. Summary of the invention
[0006] The object of the present invention is to provide a PBAT foam material and a preparation method thereof. By regulating the PBAT synthesis process, changing the sequence structure and distribution of different segments on the PBAT molecular chain, and combining the supercritical carbon dioxide solid-state foaming process, PBAT foam materials with different mechanical properties (strength and hardness) can be prepared to be suitable for cushioning packaging materials for different packaged items and under different transportation and storage environment conditions.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a PBAT foam material comprises the following steps:
[0009] S1. Blending terephthalic acid and adipic acid with 1,4-butanediol respectively to obtain PTA / BDO slurry and AA / BDO slurry; then esterifying the PTA / BDO slurry and the AA / BDO slurry respectively to obtain butylene phthalate oligomer and butylene adipate oligomer;
[0010] S2, mixing butylene terephthalate oligomer and butylene adipate oligomer and further esterifying them to obtain PBAT oligomer; then polycondensing the PBAT oligomer, pelletizing and drying it to obtain PBAT particles;
[0011] S3, vacuum-drying the PBAT particles and making a plate, then placing it in a reactor and filling it with a supercritical fluid to swell it and then release the pressure to foam it, so as to obtain a PBAT foam material.
[0012] Preferably, in step S1, the molar ratio of terephthalic acid to adipic acid is (0.46-0.49):(0.51-0.54).
[0013] Preferably, in step S1, the conditions for esterification of PTA / BDO slurry are: 230-245° C., vacuum pressure 55-65 kPa, 200-250 min;
[0014] The conditions for esterification of AA / BDO slurry are: 170-210°C, vacuum pressure 80-100 kPa, 170-250 min;
[0015] Catalysts were added during the esterification of PTA / BDO slurry and AA / BDO slurry. The catalyst was a mixture of tetrabutyl titanate and triethyl phosphate in a mass ratio of (3-7):1, and the added amount accounted for 50-200 ppm by weight in the raw materials.
[0016] Preferably, in step S2, the esterification conditions are: 230-245° C., vacuum pressure 55-65 kPa, 140-220 min.
[0017] Preferably, in step S2, the polycondensation conditions are: first react at 230-250° C. and vacuum pressure of 2-5 kPa for 210-240 min; then react at 235-250° C. and vacuum pressure of 150-250 Pa for 210-270 min.
[0018] Preferably, in step S3, the vacuum drying conditions are: 50-70° C., 6-9 h.
[0019] Preferably, in step S3, the supercritical fluid is carbon dioxide; 90-100°C, 12-15MPa.
[0020] A PBAT foam material is prepared by any of the above methods.
[0021] One method to predict the mechanical properties of PBAT foam materials by NMR is to compare the ratio of TBT sequence to ABA sequence on the PBAT molecular chain. If the ratio is lower than 0.6 or higher than 0.8, the hardness and strength of the resulting material will be reduced.
[0022] Preferably, the method for calculating the ratio of TBT sequence to ABA sequence on the PBAT molecular chain is as follows: the ratio of the integrated area of the signal corresponding to the triplet peak centered at 4.42 ppm to the integrated area of the signal corresponding to the triplet peak centered at 4.07 ppm in the NMR hydrogen spectrum of PBAT is calculated.
[0023] The beneficial effects of the present invention are:
[0024] The ratio and distribution of the four sequence structures of TBT, TBA, ABT, and ABA on the PBAT molecular chain can be regulated through the synthesis process. Even when the feed ratio of the dibasic acid PTA and AA is the same, the content of BA and BT segments in PBAT will not be significantly changed, but the ratio and distribution of the four sequence structures of TBT, TBA, ABT, and ABA on the molecular chain will be changed, which will have a significant difference on the final foaming result. The lower the TBT sequence content and the higher the ABA sequence content in the molecular chain, the lower the hardness and strength of the resulting material.
[0025] The present invention regulates the ratio and distribution of the four sequence structures of TBT, TBA, ABT and ABA on the PBAT molecular chain through a synthesis process, and combines a supercritical carbon dioxide solid-state foaming process to prepare a foaming material with different mechanical characteristics. The molecular chain structure of PBAT is changed during the PBAT synthesis process, and the sequence distribution of the four sequence structures of TBT, TBA, ABT and ABA is regulated, which has the following advantages:
[0026] 1. Regulate the melting and crystallization behavior of PBAT. Different TBT, TBA, ABT, and ABA sequence structure distributions can bring different crystallinity and melting points to the PBAT matrix.
[0027] 2. Regulate the molecular weight and distribution of PBAT. Different synthesis processes will lead to different molecular weight results.
[0028] 3. Regulate the cell structure during the foaming process. During the foaming process, the crystal area can serve as a cell nucleation site to increase the cell density. The higher the content of TBT rigid sequence structure and the lower the content of flexible sequence structure ABA, the more difficult it is to stretch the cells during the cell growth stage, reducing the cell size; in the cell stability stage, the cells are more stable and less likely to shrink.
[0029] 4. Regulate the mechanical properties of PBAT foaming materials. Different cell structures bring different mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the molecular chain structure of PBAT;
[0031] Figure 2 is the NMR hydrogen spectrum of PBAT;
[0032] Figure 3 This is the pore morphology of PBAT foam material. DETAILED DESCRIPTION
[0033] PBAT-1 synthesis process:
[0034] 1. Feeding and pulping: The raw materials PTA (terephthalic acid) and AA (adipic acid) for PBAT production are measured by weighing and measuring instruments, and enter the silo by their own weight, and PTA and BDO (1,4-butanediol), AA and BDO are respectively configured into PTA / BDO slurry and AA / BDO slurry with the required molar ratio. Among them, PTA, AA, and BDO are proportioned according to the molar ratio of 0.49:0.51:>1, and BDO is added in excess in PTA / BDO slurry and AA / BDO slurry.
[0035] 2. Esterification reaction: The prepared slurry is continuously delivered to the esterification reactor by the slurry delivery metering pump.
[0036] PTA esterification: PTA / BDO slurry was reacted in a vertical reactor equipped with a stirring device. The reaction time was 210 min. The temperature was set at 235° C. and the vacuum pressure was set at 60 kPa to obtain butylene terephthalate (BHBT) oligomers.
[0037] AA esterification: AA / BDO slurry was reacted in a vertical reactor equipped with a stirring device. The reaction time was 180 min, the temperature was set to 180° C., and the vacuum pressure was set to 90 kPa to obtain butanediol adipate (BHAT) oligomers.
[0038] Catalysts were added in both the PTA esterification and AA esterification stages. The catalysts were tetrabutyl titanate and triethyl phosphate mixed in a mass ratio of 5:1. The amount added was calculated based on the mass percentage of the theoretical yield of the prepared polybutylene terephthalate, and 100 ppm was added for each.
[0039] Second esterification: The PTA esterification product and the AA esterification product were further esterified in the second esterification kettle (vertical fully mixed reactor), the reaction time was 150 min, the temperature was set at 235° C., and the vacuum pressure was set at 60 kPa.
[0040] 3. Pre-polycondensation reaction: The oligomers sent from the esterification process are subjected to the first polycondensation in the pre-polycondensation kettle. The reaction time is 210 min, the temperature is set to 235°C, and the vacuum pressure is set to 2 kPa.
[0041] 4. Final polycondensation reaction: The prepolymer sent from the pre-polycondensation process is subjected to final polycondensation reaction in a final polycondensation kettle. The reaction time is 210 min, the temperature is set to 240° C., and the vacuum pressure is set to 200 Pa.
[0042] 5. Melt granulation: After production is completed, underwater pelletizing and drying are carried out.
[0043] Foaming process:
[0044] First, different PBAT particles were dried in a vacuum oven at 60°C for 8 hours, and then pressed at 160°C using a flat vulcanizer to produce a 3.4mm thick sheet. Then, rectangular blocks with a side length of 15mm were cut and placed in a high-temperature and high-pressure reactor with supercritical carbon dioxide as a physical foaming agent. After swelling for 1 hour under the process conditions of 95°C and 14MPa, the pressure was quickly released and foamed within 5 seconds to obtain a PBAT microporous foam material.
[0045] PBAT-2 synthesis process:
[0046] 1. Feeding and pulping: The raw materials PTA (terephthalic acid) and AA (adipic acid) for PBAT production are measured by weighing and metering instruments, and enter the silo by their own weight, and PTA and BDO (1,4-butanediol), AA and BDO are respectively configured into PTA / BDO slurry and AA / BDO slurry with the required molar ratio. Among them, PTA, AA, and BDO are proportioned according to the molar ratio of 0.48:0.52:>1, and BDO is added in excess in PTA / BDO slurry and AA / BDO slurry.
[0047] 2. Esterification reaction: The prepared slurry is continuously delivered to the esterification reactor by the slurry delivery metering pump.
[0048] PTA esterification: PTA / BDO slurry was reacted in a vertical reactor equipped with a stirring device. The reaction time was 210 min. The temperature was set at 235° C. and the vacuum pressure was set at 60 kPa to obtain butylene terephthalate (BHBT) oligomers.
[0049] AA esterification: AA / BDO slurry was reacted in a vertical reactor equipped with a stirring device. The reaction time was 180 min, the temperature was set to 180° C., and the vacuum pressure was set to 90 kPa to obtain butanediol adipate (BHAT) oligomers.
[0050] Catalysts were added in both the PTA esterification and AA esterification stages. The catalysts were tetrabutyl titanate and triethyl phosphate mixed in a mass ratio of 5:1. The amount added was calculated based on the mass percentage of the theoretical yield of the prepared polybutylene terephthalate, and 100 ppm was added for each.
[0051] Second esterification: The PTA esterification product and the AA esterification product were further esterified in the second esterification kettle (vertical fully mixed reactor), the reaction time was 150 min, the temperature was set at 235° C., and the vacuum pressure was set at 60 kPa.
[0052] 3. Pre-polycondensation reaction: The oligomers sent from the esterification process are subjected to the first polycondensation in the pre-polycondensation kettle. The reaction time is 210-240 minutes, the temperature is set to 235°C, and the vacuum pressure is set to 2kPa.
[0053] 4. Final polycondensation reaction: The prepolymer sent from the pre-polycondensation process is subjected to final polycondensation reaction in a final polycondensation kettle. The reaction time is 210 min, the temperature is set to 240° C., and the vacuum pressure is set to 200 Pa.
[0054] 5. Melt granulation: After production is completed, underwater pelletizing and drying are carried out.
[0055] Foaming process:
[0056] First, different PBAT particles were dried in a vacuum oven at 60°C for 8 hours, and then pressed at 160°C using a flat vulcanizer to produce a 3.4mm thick sheet. Then, rectangular blocks with a side length of 15mm were cut and placed in a high-temperature and high-pressure reactor with supercritical carbon dioxide as a physical foaming agent. After swelling for 1 hour under the process conditions of 95°C and 14MPa, the pressure was quickly released and foamed within 5 seconds to obtain a PBAT microporous foam material.
[0057] PBAT-3 synthesis process:
[0058] 1. Feeding and pulping: The raw materials PTA (terephthalic acid) and AA (adipic acid) for PBAT production are measured by weighing and measuring instruments, and enter the silo by their own weight, and PTA and BDO (1,4-butanediol), AA and BDO are respectively configured into PTA / BDO slurry and AA / BDO slurry with the required molar ratio. Among them, PTA, AA, and BDO are proportioned according to the molar ratio of 0.47:0.53:>1, and BDO is added in excess in PTA / BDO slurry and AA / BDO slurry.
[0059] 2. Esterification reaction: The prepared slurry is continuously delivered to the esterification reactor by the slurry delivery metering pump.
[0060] PTA esterification: PTA / BDO slurry was reacted in a vertical reactor equipped with a stirring device. The reaction time was 210 min. The temperature was set at 235° C. and the vacuum pressure was set at 60 kPa to obtain butylene terephthalate (BHBT) oligomers.
[0061] AA esterification: AA / BDO slurry was carried out in a vertical reactor equipped with a stirring device. The reaction time was 180 min, the temperature was set to 180 °C, and the vacuum pressure was set to 90 kPa to obtain butanediol adipate (BHAT) oligomers.
[0062] Catalysts were added in both the PTA esterification and AA esterification stages. The catalysts were tetrabutyl titanate and triethyl phosphate mixed in a mass ratio of 5:1. The amount added was calculated based on the mass percentage of the theoretical yield of the prepared polybutylene terephthalate, and 100 ppm was added for each.
[0063] Second esterification: The PTA esterification product and the AA esterification product were further esterified in the second esterification kettle (vertical fully mixed reactor), the reaction time was 150 min, the temperature was set at 235° C., and the vacuum pressure was set at 60 kPa.
[0064] 3. Pre-polycondensation reaction: The oligomers sent from the esterification process are subjected to the first polycondensation in the pre-polycondensation kettle. The reaction time is 210 min, the temperature is set to 235°C, and the vacuum pressure is set to 2 kPa.
[0065] 4. Final polycondensation reaction: The prepolymer sent from the pre-polycondensation process is subjected to final polycondensation reaction in a final polycondensation kettle. The reaction time is 210 min, the temperature is set to 240° C., and the vacuum pressure is set to 200 Pa.
[0066] 5. Melt granulation: After production is completed, underwater pelletizing and drying are carried out.
[0067] Foaming process:
[0068] First, different PBAT particles were dried in a vacuum oven at 60°C for 8 hours, and then pressed at 160°C using a flat vulcanizer to produce a 3.4mm thick sheet. Then, rectangular blocks with a side length of 15mm were cut and placed in a high-temperature and high-pressure reactor with supercritical carbon dioxide as a physical foaming agent. After swelling for 1 hour under the process conditions of 95°C and 14MPa, the pressure was quickly released and foamed within 5 seconds to obtain a PBAT microporous foam material.
[0069] NMR analysis
[0070] Nuclear magnetic resonance (NMR) has been proven to be the most effective method for characterizing the sequence of copolymer monomers. It can be used to analyze the sequence distribution in the PBAT molecular chain and measure and reveal its exact ratio. Figure 1 As shown. In the terpolymer PBAT molecular chain, theoretically, the B unit exists in four sequence structures, namely TBT, TBA, ABT, and ABA. Figure 2 Draw the PBAT 1 An overall view of H NMR chemical shifts, where the peaks and the corresponding chemical environments of carbon and hydrogen atoms can be identified by the letters near the peaks and Figure 1 The T unit or A unit has a significant effect on the hydrogen atoms on the methylene in the connected B unit. Signal f is given by the hydrogen atoms connected to the two central carbons of tetramethylene glycol, and signal d is given by the hydrogen atoms connected to the two side carbons of tetramethylene glycol, making these hydrogen atoms 1 The chemical shifts in the H NMR spectra show large differences ( Figure 2Signals d and f will show four types of signals, which are caused by the different possibilities of tetramethylene glycol / dicarboxylic acid connection mode in the copolymer, two butanediol (B) protons (OCH 2 …) and (OCH 2 CH 2 ...) are very sensitive to the doublet effect and therefore split into four multiplets. However, in the sequence distribution analysis, only the signals appearing in the signal d range (4.5-4.00 ppm) were used that were well separated from the protons of the hexanediyl (A) and thus more easily distinguishable. 1 The relevant sequences of the H NMR spectra are given in Table 1.
[0071] Table 1 PBAT 1 H NMR chemical shifts and corresponding structural sequences
[0072]
[0073] Note: The abbreviation s represents a singlet, t represents a triplet, and m represents a multiplet.
[0074] Therefore, the concentration of 8.08 ppm (benzene ring, signal c) and 2.31 ppm (-OCOCH 2 ..., the signal area under signal e) is used to determine terephthalic acid (f BT ) and adipic acid (f BA ) can be expressed as the content of BT and BA segments, respectively, and the calculation formula is as follows:
[0075]
[0076]
[0077] Since the chemical shifts of hydrogen atoms on the α-methylene group (i.e., the methylene group connected to the O atom) of the B unit in different sequence structures are significantly different, the integral areas of the signals corresponding to the triplet peak regions centered at ~4.42, ~4.37, ~4.13, and ~4.07 ppm are proportional to the molar fractions corresponding to the different unit sequences of TBT, TBA, ABT, and ABA, respectively. Therefore, the molar fractions of the four different sequence structures in the molecular chain can be calculated by the integral areas at their signals d. The calculation formula is as follows:
[0078]
[0079]
[0080]
[0081]
[0082] By similar calculation methods, the sequence structure of the synthesized PBAT polymer at different T / A unit feed molar ratios was investigated, and the composition and sequence distribution analysis of the PBAT samples are summarized in Table 2. The results also show that the polymer composition is completely consistent with the feed monomer ratio.
[0083] Table 2 Composition and sequence distribution of PBAT synthetic polymers
[0084]
[0085] Molecular weight analysis
[0086] The molecular weight and distribution curve of PBAT were determined by GPC, and the results are summarized in Table 3. The order of molecular weight and polydispersity index is PBAT-2>PBAT-3>PBAT-1.
[0087] Table 3 PBAT molecular weight and distribution measured by GPC
[0088]
[0089] Crystallization thermal analysis
[0090] The secondary temperature rise curve of PBAT was tested by DSC, and the corresponding crystallization thermal analysis results are shown in Table 4. As can be seen from Table 4, with the f TBT / f ABA As the ratio increases, the melting point of PBAT also increases accordingly. This is because the sequence structure content of the T-containing unit with a higher melting point increases, while the sequence structure content of the A-containing unit with a lower melting point decreases. However, the crystallinity will first increase and then decrease. This is because the molecular weight first increases and then decreases, while the order and regularity of the molecular chain sequence structure first increases and then decreases.
[0091] Table 4 Crystallization thermal analysis results of PBAT
[0092]
[0093] Foaming behavior analysis
[0094] Figure 3 The foaming temperature is 95℃, CO 2 Electron micrographs of different PBAT cell structures after sample shrinkage stabilization under the same foaming conditions such as saturation pressure 14 MPa and saturation time 1 h (magnification 1000 times, scale 80 μm). The cell structure statistics are shown in Table 5.
[0095] The initial expansion ratio of PBAT-1 is the largest, about 16 times, and its expansion ratio after stabilization is about 9 times, and the shrinkage rate is the largest, about 44%. This is because the rigid sequence structure of PBAT-1 TBTMinimal, flexible sequence structure f ABA The largest molecular chain of PBAT-1 is the softest. The molecular chain is more easily stretched during the cell growth stage of the foaming process. The foaming material shrinks severely and takes a longer time to recover. At the same time, the existence of the crystal region can serve as a nucleation site. The random degree r of the PBAT-1 molecular chain is the largest and the crystallinity is the lowest. Therefore, the average diameter of the PBAT-1 cell is the largest, about 51 μm, and the cell density is the smallest, which is 7.5×10 7 cells / cm 3 .
[0096] The initial expansion ratio of PBAT-2 is the smallest, slightly less than 10 times, and its expansion ratio is the smallest after stabilization, about 7 times, and the shrinkage rate is 22%. This is because the rigid sequence structure of PBAT-2 TBT Increased, flexible sequence structure f ABA The molecular chain rigidity of PBAT-2 increases, the molecular chain stretching degree decreases during the cell growth stage, and the foam shrinkage degree slows down greatly. In addition, PBAT-2 has the highest crystallinity. Therefore, the average cell diameter of PBAT-2 is the smallest, about 23μm, and the cell density is the largest, which is 7.4×10 8 cells / cm 3 .
[0097] The initial expansion ratio of PBAT-3 is slightly greater than 10 times, and its expansion ratio after stabilization is about 8 times, with a shrinkage rate of 27%. This is because although PBAT-3 is compared with PBAT-2, the rigid sequence structure f TBT Slightly larger, flexible sequence structure f ABA The rigidity of PBAT-3 molecular chain is slightly increased, but the molecular weight of PBAT-3 is smaller than that of PBAT-2, so the crystallinity of PBAT-3 is slightly smaller than that of PBAT-2. Therefore, the number of nuclei in the pore nucleation stage is less than that of PBAT-2, and the degree of stretching of the molecular chain in the pore growth stage is slightly increased. Therefore, the average pore diameter and pore density of PBAT-3 are in the middle.
[0098] Table 5 Statistical results of pore structure of PBAT foaming materials
[0099]
[0100]
[0101] Mechanical behavior analysis
[0102] The test results of relevant mechanical properties such as compressive strength, compression buffer energy absorption efficiency, Young's modulus, and Shore hardness of PBAT foam materials are summarized in Table 6.
[0103] PBAT-2 has the highest compressive strength (0.32MPa), the highest energy absorption efficiency (0.31), the highest Young's modulus (2.6MPa), and the highest Shore C hardness (55) at 50% compressive strain. Next, PBAT-3 has a compressive strength of 0.29MPa, an energy absorption efficiency of 0.28, a Young's modulus of 2.3MPa, and a Shore C hardness of 53 at 50% compressive strain. PBAT-1 has a compressive strength of 0.14MPa, an energy absorption efficiency of 0.24, a Young's modulus of 1.0MPa, and a Shore C hardness of 35 at 50% compressive strain.
[0104] This also corresponds to the foaming result of PBAT. Under the same conditions, the lower the foaming ratio, the smaller the pore size, the greater the cell density, the thicker the cell wall per unit area, and the more prisms, the stronger the resistance of the cell to load bending deformation, so the compressive strength, Young's modulus and hardness of the material are. Under the action of the compressive load, the force applied to the foam will cause the energy to be converted into potential energy or heat energy, and the absorption of energy is achieved in this way. Under the same compression deformation, PBAT-2 with greater compressive strength can withstand greater compressive stress, so it absorbs more energy and has a higher energy absorption efficiency. Under the same low compression stress (<~0.2MPa), the PBAT-1 cell wall with lower compressive strength has a greater degree of bending deformation, so it has more absorption capacity and a higher energy absorption efficiency; under the same high compression stress (>~0.3MPa), PBAT-1 with lower compressive strength has already reached the maximum deformation degree, and PBAT-2 with higher compressive strength has not yet reached it at this time, so PBAT-2 can still continue to absorb energy and improve energy absorption efficiency. Therefore, PBAT foam materials with different mechanical properties can be selected according to different stress environments, packaging items, etc.
[0105] Table 6 PBAT foam material mechanical properties test results
[0106]
[0107] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. A method for preparing a PBAT foam material, characterized in that: The steps include: S1. Blending terephthalic acid and adipic acid with 1,4-butanediol respectively to obtain PTA / BDO slurry and AA / BDO slurry; and then esterifying the PTA / BDO slurry and the AA / BDO slurry respectively to obtain butylene terephthalate oligomer and butylene adipate oligomer; S2, mixing butylene terephthalate oligomer and butylene adipate oligomer and further esterifying them to obtain PBAT oligomer; then polycondensing the PBAT oligomer, pelletizing and drying it to obtain PBAT particles; S3, vacuum-drying the PBAT particles and making a plate, then placing it in a reactor and filling it with a supercritical fluid to swell it and then release the pressure to foam it, so as to obtain a PBAT foam material.
2. The method for preparing the PBAT foam material according to claim 1, characterized in that: In step S1, the molar ratio of terephthalic acid to adipic acid is (0.46-0.49):(0.51-0.54).
3. The method for preparing the PBAT foam material according to claim 1, characterized in that: In step S1, the conditions for esterification of PTA / BDO slurry are: 230-245° C., vacuum pressure 55-65 kPa, 200-250 min; The conditions for esterification of AA / BDO slurry are: 170-210°C, vacuum pressure 80-100 kPa, 170-250 min; Catalysts were added during the esterification of PTA / BDO slurry and AA / BDO slurry. The catalyst was a mixture of tetrabutyl titanate and triethyl phosphate in a mass ratio of (3-7):1, and the added amount accounted for 50-200 ppm by weight in the raw materials.
4. The method for preparing the PBAT foam material according to claim 1, characterized in that: In step S2, the esterification conditions are: 230-245° C., vacuum pressure 55-65 kPa, 140-220 min.
5. The method for preparing the PBAT foam material according to claim 1, characterized in that: In step S2, the polycondensation conditions are: first react at 230-250° C. and vacuum pressure of 2-5 kPa for 210-240 min; then react at 235-250° C. and vacuum pressure of 150-250 Pa for 210-270 min.
6. The method for preparing the PBAT foam material according to claim 1, characterized in that: In step S3, the vacuum drying conditions are: 50-70° C., 6-9 h.
7. The method for preparing the PBAT foam material according to claim 1, characterized in that: In step S3, the supercritical fluid is carbon dioxide; The swelling conditions are: 90-100°C, 12-15MPa.
8. A PBAT foam material, characterized in that: The method is prepared by any one of claims 1 to 8.
9. A method for predicting the mechanical properties of PBAT foaming materials by NMR, characterized in that: It compares the ratio of TBT sequence to ABA sequence on the PBAT molecular chain. If the ratio is lower than 0.6 or higher than 0.8, the hardness and strength of the resulting material will decrease.
10. The method for predicting the mechanical properties of PBAT foaming materials by NMR according to claim 9, characterized in that: The method for calculating the ratio of TBT sequence to ABA sequence on the PBAT molecular chain is as follows: the ratio of the integrated area of the signal corresponding to the triplet peak centered at ~4.42ppm to the integrated area of the signal corresponding to the triplet peak centered at ~4.07ppm in the NMR hydrogen spectrum of PBAT is calculated.
Citation Information
Cited By
PBAT (poly (butylene adipate-co-terephthalate)) alloy, preparation method of PBAT alloy, foamed sheet and preparation method of foamed sheet
CN120118484A